2017
DOI: 10.3233/jad-160845
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Compensation as a Probable Cause of Prolonged Mild Cognitive Impairment in Alzheimer’s Disease: Implications from a Transgenic Mouse Model of the Disease

Abstract: Alzheimer's disease (AD) is a slow, progressive neurodegenerative disease in which cognitive decline takes place over a period of several years with a very variable period of mild cognitive impairment (MCI) and, in some cases, relatively long period before progression to dementia. The cognitive deficit during MCI is probably due to neuronal loss, an intermediate level of amyloid-β (Aβ) plaques and neurofibrillary tangles (NFT) and synaptosis, which is interrupted with a transient compensatory increase. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Although these findings could have been expected in light of the lack of massive neuronal loss in the cortex and the hippocampus of 3×Tg-AD mice [23], one prior study reported significant reduced synaptophysin levels in the cerebral cortex of this animal model of AD) [51]. Furthermore, a decrease in the expression of synaptophysin was observed in 3 months-old 3×Tg-AD mice associated with a trend to a compensatory increase relative to that in wild type animals in a topographic and time-dependent manner [52]. The treatment with um-PEA did not affect the marker levels in both genotypes, thus suggesting that under the present experimental conditions oral um-PEA treatment failed to exert neuroprotective effects.…”
Section: Discussionmentioning
confidence: 63%
“…Although these findings could have been expected in light of the lack of massive neuronal loss in the cortex and the hippocampus of 3×Tg-AD mice [23], one prior study reported significant reduced synaptophysin levels in the cerebral cortex of this animal model of AD) [51]. Furthermore, a decrease in the expression of synaptophysin was observed in 3 months-old 3×Tg-AD mice associated with a trend to a compensatory increase relative to that in wild type animals in a topographic and time-dependent manner [52]. The treatment with um-PEA did not affect the marker levels in both genotypes, thus suggesting that under the present experimental conditions oral um-PEA treatment failed to exert neuroprotective effects.…”
Section: Discussionmentioning
confidence: 63%
“…At early stages of the disease the brain attempts to repair itself by promoting dentate gyrus neurogenesis and synaptogenesis but, probably because of insufficient appropriate neurotrophic support, this attempt does not succeed beyond a limited time and the degree of dementia keeps advancing [17]. Employing 3 × Tg-AD mice as a model of this phenomenon [15], in the present study we found that by providing neurotrophic support with P021 we can rescue synaptic deficit and reverse cognitive impairment. The use of transgenic mouse models has helped understand the molecular mechanisms of AD and has facilitated preclinical studies that could lead to development of potential AD drugs.…”
Section: Discussionmentioning
confidence: 73%
“…Higher levels of SYP correlated with yet normal cognition in older people displaying extensive A brain pathology, compared to cognitively impaired AD patients . In addition, in 3xTg‐AD animal brains, SYP region‐ and time‐selective upregulation appeared even after an initial loss of synaptic components . This compensatory rise was related to partial recovery of cognitive functions, followed by SYP loss as symptoms worsened.…”
Section: Synaptic Elementsmentioning
confidence: 86%
“…29 In addition, in 3xTg-AD animal brains, SYP region-and time-selective upregulation appeared even after an initial loss of synaptic components. 37 This compensatory rise was related to partial recovery of cognitive functions, followed by SYP loss as symptoms worsened. In our own recent studies, in a model of slow-developing neuronal damage, obtained by exposing rat organotypic hippocampal slices to sub-lethal concentrations of oAβ42, we showed an initial compensatory increase in SYP levels and vesicle recycling.…”
Section: Synap Tic Elementsmentioning
confidence: 99%